2021
DOI: 10.7759/cureus.19655
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Guillain-Barre Syndrome During the Initial Symptomatic Phase of COVID-19 Disease: Coincidence or Consequence?

Abstract: Viral infections are frequently present before the clinical manifestation of Guillain-Barre syndrome (GBS). Multiple studies on coronaviruses have shown that these viruses have neurotropic characteristics, and their molecular mimicry can induce inflammatory demyelinating neuropathy. Herein, we describe a case of a GBS in an 85-year-old patient infected with SARS-CoV-2, manifested with acute progressive symmetric ascending quadriparesis, urinary dysautonomia, and dysphagia, who responded well to treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It has been shown that antibodies to SARS-CoV-2 can cross-react with peripheral myelin causing GBS ( 39 ). GBS usually manifests with a florid picture of clinical dysautonomia that includes the presence of hemodynamic instability, urinary retention, gastroplegia, paralytic ileus or refractory hypertension ( 40 ).…”
Section: The Role Of Dysautonomia In the Clinical Course Of Covid-19mentioning
confidence: 99%
“…It has been shown that antibodies to SARS-CoV-2 can cross-react with peripheral myelin causing GBS ( 39 ). GBS usually manifests with a florid picture of clinical dysautonomia that includes the presence of hemodynamic instability, urinary retention, gastroplegia, paralytic ileus or refractory hypertension ( 40 ).…”
Section: The Role Of Dysautonomia In the Clinical Course Of Covid-19mentioning
confidence: 99%
“…A recent study of 5 million patients revealed that COVID-19 survivors experienced a significant increase (up to 2,000%) in the risk of suffering from cardiovascular (infarction, arrhythmias), pulmonary (hypoxemia, dyspnea), metabolic (diabetes, dyslipidemia) and neurological (cognitive impairment, sleep disorders, cerebral infarction) conditions from 1 to 6 months post-infection ( 1 ), with the highest risk observed in patients who were critical, followed by hospitalized and asymptomatic patients ( 3 ). Subsequent studies have shown a relationship between cardiovascular sequelae of COVID-19 and development of dysautonomia ( 6 ), often a product of chronic systemic inflammation that increases sympathetic nerve activity ( 6 8 ). This dysautonomia is a component of “post-COVID Guillan-Barré syndrome” (PCGBS) which is the most recurrent type of neurological post-COVID disorder (observed in 15% of patients) ( 8 11 ) and has been linked to the neuro-psychological sequelae of long COVID, such as anxiety, depression, and cognitive impairment ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%